2019
DOI: 10.1016/j.chemosphere.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Radical oxidation of methyl vinyl ketone and methacrolein in aqueous droplets: Characterization of organosulfates and atmospheric implications

Abstract: In-cloud processing of volatile organic compounds is one of the significant routes leading to secondary organic aerosol (SOA) in the lower troposphere. In this study, we demonstrate that two atmospherically relevant α,β-unsaturated carbonyls, i.e., but-3-en-2-on (methyl vinyl ketone, MVK) and 2-methylopropenal (methacrolein, MACR), undergo sulfate radical-induced transformations in dilute aqueous systems under photochemical conditions to form organosulfates previously identified in ambient aerosols and SOA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
(60 reference statements)
2
21
1
Order By: Relevance
“…The specific reason was shown in the chemical mechanism in Figure 4a and further explored below. In addition, C 5 H 11 O 3 SO 4 − and C 4 H 7 O 3 SO 4 − could also be produced through the sulfate radical‐induced oxidation of MVK and MACR (Noziere et al, 2010; Schindelka et al, 2013; Wach et al, 2019). This fact could be confirmed by strong correlations ( r ≥ 0.59, p < 0.01) between isoprene‐derived OSs and oxidation products (MVK + MACR) in summer (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…The specific reason was shown in the chemical mechanism in Figure 4a and further explored below. In addition, C 5 H 11 O 3 SO 4 − and C 4 H 7 O 3 SO 4 − could also be produced through the sulfate radical‐induced oxidation of MVK and MACR (Noziere et al, 2010; Schindelka et al, 2013; Wach et al, 2019). This fact could be confirmed by strong correlations ( r ≥ 0.59, p < 0.01) between isoprene‐derived OSs and oxidation products (MVK + MACR) in summer (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…The C5H7O7Sand C5H9O7Sspecies can be produced by photooxidation of isoprene (Surratt et al, 2008;Nestorowicz et al, 2018) and/or the oxidative aging of methyltetrol sulfate (Hettiyadura et al, 2015). The C4H7O6Scan be generated both from sulfate radical reaction with MACR/MVK (Noziè re et al, 2010; Schindelka et al, 2013;Wach et al, 2019) and isoprene photooxidation (Surratt et al, 2007a;Lin et al, 2013;Nestorowicz et al, 2018). The C5H7O7Sand C4H7O6Sare also consistent in molecular formula with the OS species formed https://doi.org/10.5194/acp-2020-784 Preprint.…”
Section: Isoprene-derived Organosulfatesmentioning
confidence: 98%
“…Multiple laboratory studies have shown that organosulfates are formed in the condensed phase from reactions between organic molecules and either a sulfate ion (SO 2− 4 ) (Iinuma et al, 2009;Minerath and Elrod, 2009) or a sulfate radical (SO •− 4 ) (Schindelka et al, 2013;Wach et al, 2019). Organosulfates have been seen to form, for instance, from oxidation products of monoterpenes (Surratt et al, 2008) and pinonaldehyde (Liggio and Li, 2006) in the presence of acidified sulfate seed and from isoprene-derived organosulfates in the presence of sulfate (Darer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%